Civilizing Violence : Satyrs on 6th-Century Greek Vases - Isler-Kerényi, Cornelia (2004)
Violence exists, it seems to be inherent in human nature, always and everywhere. It is not possible to eliminate or to hide violence permanently. How is it possible, then, to have peaceful coexistence between human beings? This problem was clearly perceived by the Greeks in the 6th century B.C. In many images painted on Greek pottery we meet the satyr, a figure embodying sexual violence, usually in the entourage of the god Dionysos. We follow the satyr from his first appearance in art until the moment when a new genre of comic drama, the Satyr Play, was introduced in Athens. The vase-paintings illustrate how a figure embodying violence relates to a god whose main characteristic was to establish peace and stability. In the view of the Greeks it was possible to integrate violence in society by allowing it to express itself in a playful and creative way.